1987
DOI: 10.3109/00207458709043321
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study of Neuropsychological and Psychosocial Factors in Asymptomatic Individuals at Risk for Htlv-III/Lav Infection in a Methadone Program: Preliminary Findings

Abstract: To test the hypothesis that cognitive impairment may be present early in the course of HTLV-III/LAV infection, intravenous drug abusers (IDVAs) without overt symptoms of AIDS related illness were tested with standard neuropsychological and psychosocial measures. This study is the baseline for a prospective longitudinal study of the natural history of HTLV-III/LAV infection in this high risk population. Of 211 subjects initially evaluated, 70 (33%) were HTLV-III/LAV seropositive and 141 (67%) were seronegative.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0
2

Year Published

1988
1988
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(15 citation statements)
references
References 10 publications
1
12
0
2
Order By: Relevance
“…Impaired cognitive performance has been observed in patients with AIDS and AIDS-related complex (ARC) 12 1-231. Although evidence of cognitive dysfunction has been found in asymptomatic HIV antibody-seropositive (HIVAb +) homosexual men [211 and intravenous drug users [24] and in patients with persistent generalized lymphadenopathy [2 51, other studies indicate that asymptomatic HIV-Ab + homosexual men do not demonstrate cognitive abnormalities 122, 231 and that even patients with AIDS may not show appreciable signs of dementia 1261.…”
mentioning
confidence: 99%
“…Impaired cognitive performance has been observed in patients with AIDS and AIDS-related complex (ARC) 12 1-231. Although evidence of cognitive dysfunction has been found in asymptomatic HIV antibody-seropositive (HIVAb +) homosexual men [211 and intravenous drug users [24] and in patients with persistent generalized lymphadenopathy [2 51, other studies indicate that asymptomatic HIV-Ab + homosexual men do not demonstrate cognitive abnormalities 122, 231 and that even patients with AIDS may not show appreciable signs of dementia 1261.…”
mentioning
confidence: 99%
“…Con sistently, prospective studies and most crosssectional studies with strict adjustment for age and education have revealed no signifi cant differences between the neuropsychologic performance among AIDS-free HIVinfected and noninfected individuals [5,6,8,11,13,28]. Similar arguments and conclu sions apply with regard to the cognitive per formance among AIDS-free HIV-infected and noninfected individuals of minority groups [10,14,[16][17][18][19]29]. Again, studies with larger sample sizes and prospective cohorts with strict control for age and education found no substantial differences in the cognitive perfor mance of HIV-infected and noninfected indi viduals [10,14], In those large studies where some statistically significant difference of worse performance in few cognitive tests among AIDS-free HIV-infected individuals was seen, these changes in raw scores are very small and have no apparent clinical impact on day-to-day functioning [12,29], Although a concern in the generalization of the results of the effect of HIV infection on neuropsychologic performance has been the argument that less favored populations, i.e.…”
Section: Discussionmentioning
confidence: 48%
“…Several studies have assessed whether or not clinically significant cognitive impairment is present in otherwise healthy HIV-infected individuals, but results have been contradictory [2][3][4], Nevertheless, there is agreement among larger well-con trolled cohort and longitudinal follow-up studies of no significant increase in cognitive impairment during asymptomatic HIV infec tion [6,[8][9][10][13][14][15], The study populations in the majority of the above studies consist predominantly of white, well-educated, homosexual volunteers. However, considerable attention has been de voted to less educated and minority groups, mostly injecting drug users [10,[16][17][18][19]. It is well documented that factors such as age, edu cation and premorbid intellectual level affect performance in neuropsychologic tests [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It has often been stressed that these results cannot be extrapolated to other HIV-infected persons such as intravenous drug users [10]. Few studies, indeed, have concentrated on IVDUs [2,11,27] because these patients represent a heterogeneous group as regards education and exposure to drugs that affect the CNS (alcohol, opioids, etc. ); however, they are by far the largest group of HIV-positive subjects in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropsychological changes have been described in patients with AIDS or AIDS-related complex (ARC) [6,10,12,18,23,24,28], in patients in the persistent generalized lymphadenopathy stage (PGL) [9,25], and in HIV-positive, asymptomatic homosexuals and intravenous heroin addicts [6,18,27,29].…”
Section: Introductionmentioning
confidence: 99%